Prevalence and prognostic impact of left ventricular outflow tract calcification in patients with severe aortic stenosis undergoing transfemoral TAVI using second-generation devices. (25th November 2020) - Waldschmidt, L; Gossling, A; Ludwig, S; Linder, M; Voigtlaender, L; Schaefer, A; Bhadra, O; Schirmer, J; Reichenspurner, H; Blankenberg, S; Westermann, D; Seiffert, M; et al.
Abstract: Introduction: Left ventricular outflow tract (LVOT) calcification is known to be associated with adverse outcomes after TAVI in patients receiving first-generation transcatheter heart valves (THV). Second-generation THV have been shown to improve outcomes of TAVI patients. Thus, aim of this study is to assess the prevalence of LVOT calcification as well as its impact on procedural and clinical outcomes in patients with severe aortic stenosis undergoing transfemoral TAVI with second-generation THV in a real-world patient cohort. Methods: In this retrospective single-center analysis patients receiving transfemoral TAVI with second-generation THV for the treatment of aortic stenosis (AS) between 05/2012 and 06/2018 and with adequate CT data were included (n=836). Amount of LVOT calcification was measured quantitatively from contrast-enhanced multislice CT using a dedicated software. Baseline characteristics and outcomes were compared according to presence of significant LVOT calcification (none/≤10 mm 3 vs. >10 mm 3 ). Procedural and clinical outcome were assessed in accordance with VARC-2 criteria. All-cause mortality was assessed by Kaplan-Meier method, median follow-up was 1.4 years. Results: Significant LVOT calcification was present in 37.0% of patients. Patients with LVOT calcification were older (all results as follows without (w/o) vs. with (w) LVOT calcification: 81.4 (77.1, 84.8) vs. 82.3 (78.0, 86.3) years, p=0.006), but presented similar STS scores compared to those without LVOT calcification (5.4±4.7 vs. 5.4±3.5%, p=0.94). Moreover, patients with LVOT calcification had higher mean transvalvular gradients at baseline (30.0 (21.0, 41.0) vs. 37.0 (25.7, 47.0) mmHg, p<0.001) and higher aortic valve calcium volume (380.7 (226.8, 632.1) vs. 663.6 (364.5, 1070.3) mm 3, p<0.001). There were no significant differences in rate of device success (97.0 vs. 94.2%, p=0.11), renal failure (2.6 vs. 2.3%, p=1.00), myocardial infarction (0.9 vs. 1.2%, p=1.00) or rate of permanent pacemaker implantation at 30 days after TAVI (16.6 vs. 17.2%, p=0.91). However, rate of TIA/stroke was significantly higher in patients with LVOT calcification (2.1 vs. 6.2%, p=0.0098). Furthermore, patients with LVOT calcification had a higher rate of more than mild paravalvular leakage at discharge (3.8 vs. 7.6%, p=0.033). Rate of 1 year all-cause mortality (17.8 vs. 21.2%, p=0.23) was not significantly different between both groups. Conclusions: Significant LVOT calcification is present in a substantial proportion of patients receiving TAVI. In such patients, higher rates of cerebrovascular events and more than mild PVL occurred compared to those without significant LVOT calcification even with currently available second-generation THV. Although these findings did not translate into higher mortality rates in the present study, they underline the need for further optimization of THV technology in order to improve outcomes among all TAVI patients. Funding Acknowledgement: Type of funding source: None